Peningkatan Kualitas Pelayanan Administrasi Kependudukan Melalui Program Kalimasada Untuk Mewujudkan Warga Tertib Adminduk di Kelurahan Medokan Semampir - Triya Nur Fadila; Ni Made Ida Pratiwi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
One important aspect in the orderly and orderly administration of government is population administration. However, there are still problems related to irregularities in population administration, such as the existence of population documents that are incomplete or do not correspond to actual current conditions. To overcome this, the Population and Civil Registration Service of the City of Surabaya created an innovative Kalimasada Program (Environmentally Aware Population Administration Area). Medokan Semampir Subdistrict is participating in implementing the Kalimasada program which aims to improve the quality of population administration services and create an orderly population administration for citizens. This program involves outreach activities, data collection, population administration services, field surveys, as well as evaluation and monitoring. The results of the Kalimasada program in Medokan Semampir Subdistrict include increasing public awareness, updating population data, increasing the number of ownership of population documents, improving the quality of population administration services, and active community involvement. Thus, the Kalimasada program has proven to be effective in realizing orderly population administration in Medokan Semampir Village.